Aves, province of Guizhou, China - Roger Boyd; Árpád Nyári; Brett Benz; Guojun Chen (Check List, 2008)
We report our inventories of birds observed and collected at three field sites from the province of Guizhou, southeastern China. Our findings detailed herein complement our previous ornithological surveys from Guangxi province, as part of a comprehensive biotic survey of the region. Of 153 total bird species recorded, 17 were new for the province, among which several taxa of conservational importance, such as: Golden Pheasant Crysolophus pictus, Tawny Fish-Owl Ketupa flavipes, Black-breasted Thrush Turdus dissimilis, Fujian Flycatcher Niltava davidii, Red-tailed Laughingthrush Garrulax milnei, and Slaty Bunting Latoucheornis siemsseni. These records provide the most recent insight into the current status of the habitats and the avian biodiversity of an important, yet sparsely surveyed and reported biogeographic region.